2018
DOI: 10.1111/cjag.12186
|View full text |Cite
|
Sign up to set email alerts
|

How to fight against southern pine beetle epidemics: An insurance approach

Abstract: The southern pine beetle (SPB) is among the leading biological agents killing southern pine species in the eastern United States. In light of recognized spatiotemporal autocorrelation in SPB outbreaks, we devise a spatiotemporal block bootstrapping method that can be applied to analyze spatiotemporally dependent infestations. We also identify the relevant risk determinants and evaluate their impacts on the frequency of SPB outbreaks. For example, we find forest type, climate, and natural disasters like storm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…However, storms are also largely studied, especially in Europe [18,22,33,53], and hurricanes in Honduras [43]. Pine beetles are rarely studied [27]. Finally, some articles deal with multiple risks at the same time, either questioning the willingness-to-pay for several risks [31] or dealing with their cumulative aspect [8].…”
Section: The Risks Considered: From Wildfire In Us To Storm In Europementioning
confidence: 99%
See 1 more Smart Citation
“…However, storms are also largely studied, especially in Europe [18,22,33,53], and hurricanes in Honduras [43]. Pine beetles are rarely studied [27]. Finally, some articles deal with multiple risks at the same time, either questioning the willingness-to-pay for several risks [31] or dealing with their cumulative aspect [8].…”
Section: The Risks Considered: From Wildfire In Us To Storm In Europementioning
confidence: 99%
“…We observed that many articles deal with the United States [27,31,32,34,37,39,45,47,49]. They were the first to address the question of forest insurance, in particular, fire risk.…”
Section: The Countries Where Forest Insurance Is An Issue: Europe ...mentioning
confidence: 99%